(3JLQjO GdRhGFO hJbQjH GdahGFOs - (3GdeRLO , CMeO Hf YeQ Hf eMeO GdSjaj GdeOGOj, Uaj GdOjf,J (B930 (3g` s
(3ChdgG (B:s
(3cJGH GdfcGM bGd GdeGhQOi cGf jdRe QShd Gddg Udi Gddg Ydjg hSde EPG aQV GdUdGI cGedI dGNdd ajgG s
(3BNQgG (B:s
(3ef edc CeI hgj MGed YJb GdMed GdPi Je GdcJGH HMeO Gdedc GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B188 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B34s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B227s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg TGaYi e (B9) s
Keywords: (3Gdabg GdTGaYjs